Sodium taurocholate cotransporting polypeptide is the limiting host factor of hepatitis B virus infection in macaque and pig hepatocytes. Issue 3 (18th July 2017) - Lempp, Florian A.; Wiedtke, Ellen; Qu, Bingqian; Roques, Pierre; Chemin, Isabelle; Vondran, Florian W. R.; Le Grand, Roger; Grimm, Dirk; Urban, Stephan
Abstract : Infections with the human hepatitis B virus (HBV) and hepatitis D virus (HDV) depend on species‐specific host factors like the receptor human sodium taurocholate cotransporting polypeptide (hNTCP). Complementation of mouse hepatocytes with hNTCP confers susceptibility to HDV but not HBV, indicating the requirement of additional HBV‐specific factors. As an essential premise toward the establishment of an HBV‐susceptible animal model, we investigated the role of hNTCP as a limiting factor of hepatocytes in commonly used laboratory animals. Primary hepatocytes from mice, rats, dogs, pigs, rhesus macaques, and cynomolgus macaques were transduced with adeno‐associated viral vectors encoding hNTCP and subsequently infected with HBV. Cells were analyzed for Myrcludex B binding, taurocholate uptake, HBV covalently closed circular DNA formation, and expression of all HBV markers. Sodium taurocholate cotransporting polypeptide (Ntcp) from the respective species was cloned and analyzed for HBV and HDV receptor activity in a permissive hepatoma cell line. Expression of hNTCP in mouse, rat, and dog hepatocytes permits HDV infection but does not allow establishment of HBV infection. Contrarily, hepatocytes from cynomolgus macaques, rhesus macaques, and pigs became fully susceptible to HBV upon hNTCP expression with efficiencies comparable to human hepatocytes. Analysis of cloned Ntcp from all species revealed a pronounced role of the human homologue to support HBV and HDV infection. Conclusion : Ntcp is the key host factor limiting HBV infection in cynomolgus and rhesus macaques and in pigs. In rodents (mouse, rat) and dogs, transfer of hNTCP supports viral entry but additional host factors are required for the establishment of HBV infection. This finding paves the way for the development of macaques and pigs as immunocompetent animal models to study HBV infection in vivo, immunological responses against the virus and viral pathogenesis. (Hepatology 2017;66:703–716).